2010
DOI: 10.1037/a0020389
|View full text |Cite
|
Sign up to set email alerts
|

Associations among family environment, sustained attention, and school readiness for low-income children.

Abstract: In this study, we examined the developmental pathways from children’s family environment to school readiness within a low-income sample (N = 1,046), with a specific focus on the role of sustained attention. Six distinct factors of the family environment representing maternal parenting behaviors, the physical home environment, and maternal mental health at 3 years of age were explored as independent predictors of children’s observed sustained attention as well as cognitive and behavioral outcomes at 5 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 104 publications
5
88
2
5
Order By: Relevance
“…Importantly, despite not being directly comparable due to the assessment by different tasks and metrics, these similar patterns of age-dependent improvements of performance may suggest common underlying processes in EF and in SA. Alternatively, an independent factor may fuel development in both EF and SA concurrently with parental behavior, or, more broadly family environment, potentially accounting for shared variance in EF and SA (Graziano, Calkins, & Keane, 2011;Razza, Martin, & Brooks-Gunn, 2010). In any case, results may thus be interpreted as indicating an ongoing yet probably not linear development in both the EF components and SA until almost 9 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, despite not being directly comparable due to the assessment by different tasks and metrics, these similar patterns of age-dependent improvements of performance may suggest common underlying processes in EF and in SA. Alternatively, an independent factor may fuel development in both EF and SA concurrently with parental behavior, or, more broadly family environment, potentially accounting for shared variance in EF and SA (Graziano, Calkins, & Keane, 2011;Razza, Martin, & Brooks-Gunn, 2010). In any case, results may thus be interpreted as indicating an ongoing yet probably not linear development in both the EF components and SA until almost 9 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the associations observed here, while arguably robust for the reasons invoked above, were small in magnitude. Accordingly, these results should be seen as adding one piece to the complex developmental puzzle linking parenting behaviors to school readiness, which probably also includes children's attentional capacities (Razza, Martin, & Brooks-Gunn, 2010) and parentchild attachment, which has often been found to relate to parental mind-mindedness (e.g., Laranjo, Bernier, & Meins, 2008) and children's effortful control (e.g., Nordling, Boldt, O'Bleness, & Kochanska, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the studies selected used a qualitative approach (20) . With respect to study type, there was predominance of publications with higher level of evidence: one randomized clinical trial (18) and seven longitudinal studies (19,(21)(22)(23)(24)(25)(26) . The others were three cross-sectional studies (27)(28)(29) and two literature reviews: one narrative (30) and one integrative (31) .…”
Section: Analysis Of Selected Studiesmentioning
confidence: 99%
“…The survey conducted with 1046 children and their families (21) showed statistically significant correlation between sustained attention, receptive vocabulary, and environmental aspects. In this study, the authors observed that sustained attention to a particular activity was associated with better performance in receptive vocabulary for both low socioeconomic groups (low income and very low income).…”
Section: Razza Et Al (21)mentioning
confidence: 99%
See 1 more Smart Citation